Molecular Mechanisms for Herpes Simplex Virus Type 1 Pathogenesis in Alzheimer’s Disease - Harris, Steven A.; Harris, Elizabeth A. (Frontiers in Aging Neuroscience, 2018)
This review focuses on research in the areas of epidemiology, neuropathology, molecular biology, and genetics that implicates herpes simplex virus type 1 (HSV-1) as a causative agent in the pathogenesis of sporadic Alzheimer’s disease (AD). Molecular mechanisms whereby HSV-1 induces AD-related pathophysiology and pathology, including neuronal production and accumulation of amyloid beta (Aβ), hyperphosphorylation of tau proteins, dysregulation of calcium homeostasis, and impaired autophagy, are discussed. HSV-1 causes additional AD pathologies through mechanisms that promote neuroinflammation, oxidative stress, mitochondrial damage, synaptic dysfunction, and neuronal apoptosis. The AD susceptibility genes apolipoprotein E (APOE), phosphatidylinositol binding clathrin assembly protein (PICALM), complement receptor 1 (CR1), and clusterin (CLU) are involved in the HSV lifecycle. Polymorphisms in these genes may affect brain susceptibility to HSV-1 infection. APOE, for example, influences susceptibility to certain viral infections, HSV-1 viral load in the brain, and the innate immune response. The AD susceptibility gene cholesterol 25-hydroxylase (CH25H) is upregulated in the AD brain and is involved in the antiviral immune response. HSV-1 interacts with additional genes to affect cognition-related pathways and key enzymes involved in Aβ production, Aβ clearance, and hyperphosphorylation of tau proteins. Aβ itself functions as an antimicrobial peptide (AMP) against various pathogens including HSV-1. Evidence is presented supporting the hypothesis that Aβ is produced as an AMP in response to HSV-1 and other brain infections, leading to Aβ deposition and plaque formation in AD. Epidemiologic studies associating HSV-1 infection with AD and cognitive impairment are discussed. Studies are reviewed supporting subclinical chronic reactivation of latent HSV-1 in the brain as significant in the pathogenesis of AD. Finally, the rationale for and importance of clinical trials treating HSV-1-infected MCI and AD patients with antiviral medication is discussed.